Osteopenia as a target for early therapeutic intervention in the prevention of osteoporosis - Wałachowska, Anna; Alicja Tabian,; Paulina Kozłowska,; Jakub Smęt,; Aleksandra Beata Chojnacka,; Jacek Borawski,; Julia Burdon-Sajnóg,; Zofia Szymona-Kuciewicz,; Klaudia Katarzyna Bartela,; Julia Katarzyna Dusiel, (Journal of Education, Health and Sport, 2025)
Background. Osteoporosis is the most common metabolic bone disease in the world, occurring primarily in postmenopausal women and older men. The disease is usually diagnosed only after a fracture has occurred, and in a significant proportion of patients, bone mineral density (BMD) values indicate only osteopenia. Aim. The article aims to draw attention to the need for early diagnosis and appropriate intervention in people with osteopenia, to determine the appropriate moment to start treatment, and to present recommendations for prevention and treatment in different phases of the disease. Material and Methods. A literature review has been conducted using databases such as PubMed, FRAX calculator. Particular attention was paid to the most recent years of publication. Conclusions. Early diagnosis and prevention of bone mineral density disorders, as well as the implementation of appropriate treatment in the early stages of the disease can limit the development of osteoporosis and reduce the risk of fractures. According to current guidelines, pharmacological treatment of patients with osteopenia should only be considered in the presence of additional fracture risk factors. Effective implementation of therapy requires accurate diagnosis and proper classification of the patient into the appropriate fracture risk group.